Seleksi Kelapa Unggul untuk Ekspor Menggunakan Metode SAW - Shafiq Aiman Manurung; jhonson Efendi Hutagalung; Sri Rezki Maulina Azmi (Jurnal Algoritma, 2026)
The growth of the coconut industry in Indonesia presents significant opportunities for increasing exports of dried coconuts; however, the selection process for high-quality coconuts at CV. Sejati Kilang is still conducted manually and subjectively, leading to inconsistencies in quality assessment. This study aims to design and implement a decision support system based on the Simple Additive Weighting (SAW) method for the objective and efficient selection of high-quality coconuts based on five criteria: size, moisture content, cleanliness, maturity level, and physical condition. The system was developed as a web-based application using PHP and MySQL. Test results showed that Hybrid Coconuts received the highest score of 0.95, followed by Pandan Wangi Coconuts at 0.86 and Local Coconuts at 0.81. This study contributes to the development of a web-based superior coconut selection system integrated with the SAW method, resulting in a more structured, objective, and consistent evaluation process that supports rapid decision-making. However, this study is still limited in the number of alternatives and criteria, so further development is needed to improve accuracy and enable application on a larger scale.